Simulated Sanctity in Seventeenth- and Eighteenth-Century Malta - Ciappara, Frans (Studies in church history, 2011)
Revelations, apparitions, voices, stigmata and ecstasies were extraordinary phenomena and profoundly emotional, in which God was perceived as communicating with human beings through bodily phenomena. It was up to churchmen to regulate and control divine intervention in daily life and separate truth from deceit. But attempting to fulfil this pastoral duty was a complicated matter. Were these experiences authentic, really proceeding from God or were they illusions of the devil, the deceiver par excellence and able to capture human trust? Furthermore, besides the devil’s deceit, might there not also be an element of human simulation or ‘false sanctity’, that is, a mixture of lies and hypocrisy? This was the art of the actor, who makes the audience believe what is untrue. Hypocrites have one sole aim: to obtain praise and fame through the exercise of sham virtues.